Violence auprès des femmes dans les secteurs d’emploi non traditionnellement féminins et indemnisation - Marie-Josée Legault (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper describes the initial results from empirical research carried out in five organizations in different sectors of economic activity that had set up affirmative action programs to further the hiring of women in non-traditional trades (NTT). Workgroups are not, of course, the united entities some people would like them to be, and the entry of women into traditionally male working sectors has created new divisions. Although the situation is usually peaceful, violence can occur. The author begins by defining workplace violence and then describes its most common manifestations among blue-collar unionized workers, mainly in the form of sexist harassment. The paper also describes the discriminatory aspects revealed as the female victims ask for compensation for psychological injury. Following this first descriptive part, the author examines some of the strategies used by management to deal with such problems, and goes on to discuss the theoretical results before concluding with some avenues for future research.